Responses of Detoxifying, Antioxidant and Digestive Enzyme Activities to Host Shift of Bemisia tabaci (Hemiptera: Aleyrodidae) - Pan DENG; Long-jia CHEN; Zong-lei ZHANG; Ke-jian LIN; Wei-Hua MA (Journal of Integrative Agriculture, 2013)
The polyphagous B-biotype of Bemisia tabaci (Gennadius) has demonstrated a high capacity to adapt to numerous hosts from diverse plant families. To illustrate induced responses by the host plant, biochemical research on eight plant-insect interaction correlative enzymes, representing detoxifying, antioxidant and digestive pathways, were investigated. Transferring whitefly adults to Zhongmian 23 from the pre-adapted host Zhongmian 41 induced activities of carboxylesterase (by 1.80-fold), glutathione S-transferase (by 3.79-fold), proteinase (by 1.62-fold) and amylase (by 2.41-fold) activities, but decreased polyphenol oxidase (by 1.89-fold) and peroxidase (by 1.88-fold). However, transferring whitefly adults to the favorite host abutilon from Zhongmian 41 was associated with increased activities of cytochrome P450 monooxygenase (by 1.61-fold) and amylase (by 1.42-fold), and decreased activities of polyphenol oxidase (by 2.96-fold) and peroxidase (by 2.07-fold). Our results, together with previous studies, proved that multiple pathways are involved in coping with host shifts by polyphagous herbivores, and the taxonomic status and preference of the host transferred would affect which pathway would be induced. These results would represent a key challenge in developing long-term sustainable insect control strategies.